CA-125 Examination as a Predictor the Resectability of Advanced Stage of Ovarian Cancer - Muhammad, Syamel; Rudy Setiawan, Muhammad; Savannah, Aisha (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective: To describe the prompt and successful treatment of an extrauterine pregnancy case in a tertiary-level hospital in Indonesia. Methods: We report a case of prompt and successful management of unruptured tubal pregnancy in the dr. Soetomo General Hospital Surabaya. Results: A 32-years-old woman presented with lower abdominal pain and vaginal bleeding one days before admission. She was sexually active, used no contraceptives, and had a history of one miscarriage. On examination, she was hemodynamically stable. A bimanual exam revealed cervical motion tenderness and pain. A high human chorionic gonadotropin (hCG) level (1,725 IU/L) and a left-sided mass, highly suspected as an extrauterine gestational sac confirming a 6 week, 1 days age of pregnancy without sign of free fluid in the abdomen nor fetal heart rate on ultrasound, prompted diagnostic laparoscopy. We found a tubal pregnancy located on the ampullae of the left fallopian tube with minimal hemoperitoneum (50 ml). A chromopertubation test was done to ensure a patent right fallopian tube, so we did a salpingectomy. The patient recovered well and was discharged home on day 2 post-procedure. Conclusion: Early diagnosis is vital and feasible to prevent morbidity and mortality in women with ectopic pregnancy. All sexually active women complaining painful abdomen or vaginal bleeding must be examined for an ectopic pregnancy to enable early diagnosis and prompt treatment. A laparoscopic surgery done by a trained individual provided a safe and minimally invasive intervention to this case. Keywords: case report, ectopic pregnancy, laparoscopy, salpingectomy, tubal pregnancy